Financial risk measurement and management (International library of critical writings in economics, 2012)
This authoritative volume charts the origins, development, and current frontiers of financial risk management. It emphasizes the role for risk management created by real-world market imperfections, and progresses to consider stochastic financial modeling, the failure of 'normality', and time-varying volatility. Professor Diebold has selected seminal papers by leading academics which cover multiple markets (equities, bonds, etc.), univariate and multivariate perspectives, connectedness and systemic risks, and stress testing. The collection, along with an original introduction by the editor, will be of interest to academics, market participants, and policymakers, particularly as we chart a new course following the financial crisis of 2007-2008.